2023
DOI: 10.3390/healthcare11040560
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Prosocial Tendencies: Meta-Analysis of the Generalization of the Reliability of the Instrument

Abstract: The Prosocial Tendencies Measure (PTM) and its revised version (PTM-R) are used internationally to measure prosocial behaviors in different life situations. To obtain accumulated evidence of the report and the reliability of its scores, a meta-analysis of the reliability of internal consistency was performed. The databases of Web of Science (WoS) and Scopus were reviewed and all the studies that applied it from 2002 to 2021 were selected. Results: Only 47.9% of the studies presented the index of reliability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 102 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…We employed the Prosocial Tendencies Measurement Scale, developed by Kou et al (2007) , to measure prosocial behaviors. A meta-analysis indicated that the reliabilities of the PTM were acceptable ( Reig-Aleixandre et al, 2023 ). The scale comprised 26 items, each scored on a 5-point Likert scale ranging from 1 = “not true” to 5 = “certainly true.” The Cronbach’s alpha coefficient for internal consistency in this study was 0.95.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We employed the Prosocial Tendencies Measurement Scale, developed by Kou et al (2007) , to measure prosocial behaviors. A meta-analysis indicated that the reliabilities of the PTM were acceptable ( Reig-Aleixandre et al, 2023 ). The scale comprised 26 items, each scored on a 5-point Likert scale ranging from 1 = “not true” to 5 = “certainly true.” The Cronbach’s alpha coefficient for internal consistency in this study was 0.95.…”
Section: Methodsmentioning
confidence: 99%
“…Prior literature has demonstrated the influence of cognition and emotion on prosocial behavior (Rahal and Fiedler, 2022). Recent research has uncovered that music therapy might enhance prosocial behavior by affecting these two factors, especially among individuals who have undergone social exclusion (Martí-Vilar et al, 2023). Within the CAPS framework, the current study aims to integrate contextual, cognitive, and personality factors to explore their impact on prosocial behavior, particularly following experiences of social exclusion.…”
Section: Introductionmentioning
confidence: 99%